A working party report on the use of corrosion inhibitors in oil and gas production - Palmer, J. W.; Hedges, W.; Dawson, J. L. (Publications (European Federation of Corrosion), 2004)
This practical industry-oriented guide has been compiled to meet the needs of personnel employed by operators, design engineers, contractors and chemical suppliers working in the oil and gas industry. The document draws on the experience of specialists employed in various organisations and incorporates appropriate industry and in-company guidelines. Both technical and management issues are addressed and key points are provided at the end of each chapter to aid in the assimilation of the many and varied aspects that contribute to successful corrosion inhibition.